AIR MILES AND SALE: THE ABSENCE OF CONSENSUS LEGAL AND RESTRICTIONS IN COMPANY REGULATIONS AIR (REMUNOM, 2024)
Air miles have gained great legal notoriety, due to their wide use in the aviation and tourism market. However, it is observed that there is no legal consensus in conflicts related to its use and commercialization. Therefore, this research aims to analyze airline regulations, decisions related to this issue in the judiciary, and the relationship between airlines and consumers, illustrating that miles have commercial value, and require legal support to bring a legally supported equity relationship into the consumption relationship.